Symbolic Monte Carlo method applied to the identification of radiative properties of a heterogeneous material. (July 2020) - Maanane, Yassine; Roger, Maxime; Delmas, Agnès; Galtier, Mathieu; André, Frédéric
Highlights: Symbolic Monte Carlo method is applied for the identification of radiative properties of an insulating material. An inverse analysis based on SMC polynomials determines if the inverse problem is well or ill-posed. SMC polynomials allows to decrease significantly the computational cost of the inverse method. Abstract: A Symbolic Monte Carlo method (SMC) is applied to the identification of radiative properties of a heterogeneous semitransparent insulating material from measurements of directional-hemispherical transmittance and reflectance at room temperature. The polynomials obtained with SMC allow the development of a complete inverse analysis which determines if the inverse problem solution exists, is unique and stable. Moreover, the numerical efficiency of the absorption and scattering coefficients identification is improved since the radiative transfer equation is only solved once in the overall inverse iterative procedure.